Analysis Of Ipas Learning Problems In The Merdeka Curriculum At Grade V - Jannah, Iftakhul Kalimatul; Widarti, Hayuni Retno; Utama, Candra (UNIVERSITAS PAKUAN, 2024)
The implementation of the Merdeka Curriculum in Indonesia marked a fundamental change in the approach to learn, gave teachers and students more freedom with an emphasis on practice, projects and differentiation of learning. This research revealed a number of challenges in implementing the Merdeka Curriculum, especially in the context of IPAS subjects. Although the Merdeka Curriculum provided freedom, teachers were faced with obstacles such as difficulties in preparing learning tools and determining the right methods. The implementation of formative assessment as an integral part of the curriculum also showed its own complexities. Although efforts had been made to overcome the barriers, this study concluded that further evaluation was needed to measure the positive impact of Merdeka Curriculum on IPAS learning and assessed the extent to which this curriculum was able to increasing student engagement and understanding at the primary school level. IPAS learning combined Natural Science and Social Science, it required teachers who were able to integrate complex concepts, prepared teaching materials and methods that were suitable for IPAS Class V.